СТРУКТУРА СОЦІАЛЬНОГО КОНФЛІКТУ: ФІЛОСОФСЬКИЙ ВИМІР - СКАЛАЦЬКА, О. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті розглядаються структурні елементи соціального конфлікту. Автораналізує доробки західних та вітчизняних вчених, виокремлює їх основні орієнтирирозкриття причин виникнення та сутності соціального конфлікту, та на цьому ґрунтіробить власні висновки. Наголос надається на різноманітті соціальних протиріч, щопризводять до виникнення конфлікту.Скалацкая Е.В. СТРУКТУРА СОЦИАЛЬНОГО КОНФЛИКТА: ФИЛОСОФСКОЕИЗМЕРЕНИЕ В статье рассматриваются структурные элементы социальногоконфликта. Автор анализирует разработки западных и отечественных ученых, выделяетосновные ориентиры раскрытия причин возникновения и сущности социальногоконфликта, и на этом основании делает собственные выводы. Акцент делается наразнообразии социальных противоречий, которые приводят к возникновению конфликта.Ключевые слова: аналитическая модель, детерминанты, напряжение,противоречие, социальный конфликт.Skalatskaya E. STRUCTURE OF SOCIAL CONFLICT: PHILOSOPHICAL DIMENSIONThis article examines the structural elements of social conflict. The author analyzes thedevelopment of native and foreign scientists are main targets of disclosure of the causes andnature of social conflict, and on this basis makes his own conclusions. In history of social andphilosophical idea there is a variety of going near research of social conflict. Socialtransformations of end XX - beginning of XX century changed landmarks of consideration ofconflict. In existent approaches it is possible to select two basic: the first demonstratespermanent transformations, and consequently and motivations of conflicts, under act of externalterms; second - specifies on ambivalent nature of social contradictions, but not out of social andpolitical context.Key words: analytical model, determinants, tension, conflict, social conflict.